Development of Online Clearance System Using Web-Based System - Alsideiri A.; Tawafak R.M.; Alfarsi G.; Khudayer B.H.; Cob Z.C. (Institute of Electrical and Electronics Engineers Inc., 2024)
Computer Software, an Online-based clearance system, is an internet-based system that effectively manages information for colleges and universities. The aim of this study is to develop software for graduated services and follow up to replace the manual method of clearance for graduating students. The system serves as a more reliable and effective means of removing all forms of delay and enabling an understanding of the procedures involved and how to do online clearance. The data was collected from the BUC collage. the method used to develop software for easy service after graduation. The online clearance system was implemented using Basic Visual 2015 for all static and dynamic programming and MYSQL to manage the database. The finding reveals a significant use of the software. The application reveals the effectiveness and efficiency of these services' software. 2023 IEEE.